Effect of PET/CT standardized uptake values on complete response to treatment before definitive chemoradiotherapy in stage III non-small cell lung cancer - DANE, FAYSAL; ALKIŞ, HİLAL; ADLI, MUSTAFA; YUMUK, PERRAN FULDEN; ÖNEŞ, TUNÇ (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
PurposeThe standard treatment for patients with stage III non-small cell lung cancer (NSCLC), unsuitable for resection and with good performance, is definitive radiotherapy with cisplatin-based chemotherapy. Our aim is to evaluate the effect of the maximum value of standardized uptake values (SUVmax) of the primary tumor in positron emission tomography-computed tomography (PET/CT) before treatment on complete response (CR) and overall survival.MethodsThe data of 73 stage III NSCLC patients treated with concurrent definitive chemoradiotherapy (CRT) between 2008 and 2017 and had PET/CT staging in the pretreatment period were evaluated. ROC curve analysis was performed to determine the ideal cut-off value of pretreatment SUVmax to predict CR.ResultsMedian age was 58years (range 27-83years) and 66 patients were male (90.4%). Median follow-up time was 18months (range 3-98months); median survival was 23months. 1-year overall survival (OS) rate and 5-year OS rate were 72 and 19%, respectively. Median progression-free survival (PFS) was 9months; 1-year PFS rate and 5-year PFS rate were 38 and 19%, respectively. The ideal cut-off value of pretreatment SUVmax that predicted the complete response of CRT was 12 in the ROC analysis [AUC 0.699 (0.550-0.833)/P<0.01] with a sensitivity of 83%, and specificity of 55%. In patients with SUVmax<12, CR rate was 60%, while, in patients with SUV12, it was only 19% (P=0.002). Median OS was 26months in patients with pretreatment SUVmax<12, and 21months in patients with SUVmax12 (HR=2.93; 95% CI 17.24-28.75; P=0.087). CR rate of the whole patient population was 26%, and it was the only factor that showed a significant benefit on survival in both univariate and multivariate analyses.ConclusionPretreatment SUVmax of the primary tumor in PET/CT may predict CR in stage III NSCLC patients who were treated with definitive CRT. Having clinical CR is the only positive predictive factor for prolonged survival.
Keywords: Stage III; Non-small cell lung cancer; Chemoradiotherapy; PET; CT; SUVmax; POSITRON-EMISSION-TOMOGRAPHY; PROGNOSTIC VALUE; FDG-PET; F-18-FDG PET; SURVIVAL; RADIOTHERAPY; PREDICTION